Determination of groundwater pollution potential in Metro Manila using drastic approach - Pascual, Amir Y. (1992, 1992)
DRASTIC system coupled with a geologic software was used in this study to determine the location of potential areas in Metro Manila where groundwater is susceptible to pollution. The DRASTIC system was developed in the United States in 1987 by Linda Aller et. al. as a generalized vulnerability assessment method which determines regional variations in groundwater pollution potential by evaluating a set of parameters within designated hydrogeological settings. These parameters are: (1) depth-to-water; (2) net recharge; (3) aquifer media; (4) soil media; (5) topography ; (6) vadose zone media; and (7) hydraulic conductivity. These parameters are incorporated into relative ranking scheme that uses a combination of weights and ratings to produce a numerical value called Drastic Index. Metro Manila is represented by 100 drastic cells for groundwater pollution potential assessment. In this study, Drastic Index that range from 70 to 109 indicates low potential to groundwater pollution of the cell or area; index value of 110 to 129, moderately potential; and index value of 130 and above is highly vulnerable to groundwater pollution of the cell or area being evaluated. The findings in this study show that shallow groundwater table in Metros Manila is located in the vicinities of Parang, Marikina and In Fairview Park, Quezon City with an average depth of 0.5 meter and 1 meter, respectively. Vulnerable areas to ground water pollution are located in Fairview Park near La Mesa reservoir and in National Governments Center down to Capitol Homes subdivision all in Quezon City with a vulnerability index of 141 and 136, respectively.
Computer print-out.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Groundwater -- Pollution -- Philippines -- Manila metropolitan area; Groundwater -- Quality -- Management. -- Philippines -- Manila metropolitan area; Water -- Pollution potential -- Philippines